Pelatihan Massage Akupressur pada Kelompok Bidan sebagai Asuhan Komplementer pada Ibu Hamil Trimester III - Ni Gusti Ayu Pramita Aswitami; Ni Putu Mirah Yunita Udayani; I G.A. Manik Karuniadi (Jurnal Empathy Pengabdian Kepada Masyarakat, 2020)
Background: Pregnant women in third trimester 85% have complain with lower back pain. Management of back pain in pregnant women can be done by nonpharmacology, one of them with acupressure therapy. Acupressure therapy is one of complementary midwifery care services. The purpose of this activity is that midwives are able to provide complementary care in the form of acupressure therapy to improve health and reduce complaints of back pain in pregnant women. Methods: The acupressure therapy training activity was attended by 20 midwives who were held at STIKES Bina Usada Bali. This activity is carried out in 3 stages, namely the planning stage, the implementation phase and the evaluation phase. Evaluation is done by measuring knowledge using a questionnaire and acupressure practice skills using a checklist. Results: The results of community service activities indicate an increase in knowledge of midwives about acupressure therapy and an increase in the skills of midwives in conducting acupressure techniques. Conclution: It is recommended that community service providers provide training with a greater area coverage and midwives are expected to implement the results of this training to pregnant women especially those with back pain.